A Full-Length Infectious cDNA Clone of Zika Virus from the 2015 Epidemic in Brazil as a Genetic Platform for Studies of Virus-Host Interactions and Vaccine Development - Tsetsarkin, Konstantin A. (mBio, 2016)
An arthropod-borne virus, Zika virus (ZIKV), has recently emerged as a major human pathogen. Associated with complications during perinatal development and Guillain-Barré syndrome in adults, ZIKV raises new challenges for understanding the molecular determinants of flavivirus pathogenesis. This underscores the necessity for the development of a reverse genetic system based on an epidemic ZIKV strain. Here, we describe the generation and characterization in cell cultures of an infectious cDNA clone of ZIKV isolated from the 2015 epidemic in Brazil. The cDNA-derived ZIKV replicated efficiently in a variety of cell lines, including those of both neuronal and placental origin. We observed that the growth of cDNA-derived virus was attenuated compared to the growth of the parental isolate in most cell lines, which correlates with substantial differences in sequence heterogeneity between these viruses that were determined by deep-sequencing analysis. Our findings support the role of genetic diversity in maintaining the replicative fitness of viral populations under changing conditions. Moreover, these results indicate that caution should be exercised when interpreting the results of reverse-genetics experiments in attempts to accurately predict the biology of natural viruses. Finally, a Vero cell-adapted cDNA clone of ZIKV was generated that can be used as a convenient platform for studies aimed at the development of ZIKV vaccines and therapeutics.